The economics of industrial society - Morishima, Michio 1923-2004 (Cambridge University Press, 1984)
This book is a stimulating and original introduction to the economics of industrial society. It is intended for use as a student text, but will also be of interest to all those - whether students or teachers - looking for new ways of understanding the economic problems of industrialised countries. It provides an effective critique of current economic theories, and develops an original model of the economics (whether neo-classical, Marxist, or Keynesian) of modern industrial society. Throughout the book the analysis is oriented towards the solution of problems in the real world, and towards explaining the operation of economic institutions in different countries. The work looks at the way individual markets operate, the determination of foreign exchange rates, the problem of unemployment, and the fiscal and monetary policies needed to tackle unemployment. This book analyses the case of an industrial country entirely dependent on other countries for its raw materials